Review on Moringa oleifera Plant - Sharma, Shubham; Rani, Ritu; Singh, Ajeet Pal; Singh, Amar Pal (Journal of Drug Delivery and Therapeutics, 2024)
The most extensively grown species of the monogeneric, Moringaceae family, which is native to south Asia, is Moringa oleifera, sometimes known as "The Miracle Tree." The medium-sized agroforestry tree Moringa oleifera (Moringaceae) is native to south Asia but has now naturalized in many other nations. Moringa is also thought to be a treatment for malnutrition. It has several pharmacological characteristics, including antioxidant, hepatoprotective, cardioprotective, anti-inflammatory, anti-diabetic, and anti-cancer effects. It was discovered that every portion of the plant contains bioactive components. To far, over a hundred chemicals, comprising alkaloids, flavonoids, anthraquinones, vitamins, glycosides, and terpenes, have been identified from various sections of Moringa oleifera. These leaves have been used for many years in traditional medicine to treat a wide range of illnesses. These leaves have the potential to avert the plague of starvation and associated illnesses due to their potent nutritional content. In this article, we will keep an eye on Moringa Oleifera Plant overview. Keywords: Moringa Oleifera plant, Miracle Tree, Herb, Drumstick, Herbal Medicine